Participatory identification and prioritization of agri enterprises in national capital region of India - NAIN, M S; SINGH, RASHMI; SHARMA, J P; BURMAN, R R; CHAHAL, V P (The Indian Journal of Agricultural Sciences, 2015)
The rural youth are disoriented and clueless in the face of lack of income generating and employment opportunities. The problems of young men and women, as well as their vision and aspirations are essential elements of the challenges facing today’s societies and future generations. Farm and nonfarm enterprises in rural areas will be able to channelize energies of youth population in a constructive manner for regional and consequently national development. An action research project was undertaken by IARI for enhancing entrepreneurship among rural youth aiming at identification, prioritization of feasible agricultural technology, technological empowerment and hand holding for agripreneurship development in four selected villages of National Capital Region of Delhi; namely Partapur (Hapur), Hasangarh (Rohtak), Kansala (Rohtak) and Badarpur Said (Faridabad). The participatory prioritization was done involving micro screening exercise which is a very important step positioned between the project idea generation and the final decision about the most promising business idea. Micro screening exercise based on situational analysis of villages revealed that floriculture, seed production, net house cultivation, vermi compost/organic products, apiary, value addition, mushroom production and dairy enterprises excelled in order of scores gained irrespective of location. The psychological traits including need for achievement, aspirations and risk taking willingness of the potential entrepreneurs were found to be of moderate level at initial stage.